Effect of Phytase Supplementation in Diets on Nutrient Digestibility and Performance in Broiler Chicks - Santos, F. R. [UNESP]; Hruby, M.; Pierson, E. E. M.; Remus, J. C.; Sakomura, N. K. [UNESP] (Poultry Science Assoc Inc, 2008)
A performance trial was conducted with broiler chicks to Study the effect of phytase (PHY) supplementation in diets formulated With reduced AME, Ca, and P. The nutrient digestibility was determined during the 14- to 21-d and 28- to 35-d periods. The treatments consisted of 3 diets (NC1, NC2. NC3) differing ill nutrient content and each diet with Or without supplemental PHY (NC1, 0 oi 500; NC2, 0 or 750; NC3, 0 or 1,000 U of PHY/kg feed) and I positive control diet (PC). Compared with the PC diet. negative control diets (NC) resulted in lower AME and apparent ileal amino acid digestibility for some amino acids. Phytase Supplementation of the NC diets increased AME. apparent ileal amino acid digestibility, and apparent ileal crude protein digestibility. Phytase addition also increased mineral absorption in 2 1 - and 35-d-old broilers fed NC diets. Reduced nutrient digestibility appears to be I factor in the weight gain and feed intake results. Reducing Ca and P content reduced feed intake in a stepwise fashion in the NC diets. Phytase increased feed intake and generally improved nutrient digestibility, which resulted in an increase in digestible nutrient intake. Averaged across NC diets. PHY improved body weight. Bone-breaking strength was the most consistent predictor of Ca and P reduction. All NC diets had significantly lower bone-breaking strength than the PC. Phytase supplementation of the NC diets gave bone-breaking strengths that were comparable to the PC. Diets with PHY had the highest bioeconomic index.
Keywords: broiler chick; nutrient digestibility; phytase matrix